Kernel oil content and oil composition in walnut (Juglans regia L.) accessions from north‐eastern Italy. (28th August 2017) - Poggetti, Luca; Ferfuia, Claudio; Chiabà, Cristina; Testolin, Raffaele; Baldini, Mario
Abstract: BACKGROUND: Walnut oil use is currently limited by its poor oxidative stability due to the high percentage of polyunsaturated fatty acids. Modifying the oil composition may be a goal in walnut breeding to increase interest in this crop. Exploring natural variability and identifying the main environmental factors affecting oil quality are necessary in crop selection. Therefore 190 wild accessions were collected and evaluated during 2013 and 2014 for oil content and its fatty acid profile and compared with five commercial cultivars as references. RESULTS: High variation in kernel oil content and fatty acid composition was found in the native walnut. Kernel oil content ranged from 54.2 to 72.2% (w/w). The major fatty acids were linoleic (range 46.9–68.6%), oleic (10.0–25.1%), linolenic (6.9–17.6%), palmitic (3.9–11.4%) and stearic (1.1–5.2%) acids. Some accessions had oil with a fatty acid ratio very different from the reference commercial cultivars, especially the oleic acid/polyunsaturated fatty acid (PUFA) ratio. A significant linear relationship and positive correlation between the daily minimum temperature and oleic acid content was observed in the wild walnuts. CONCLUSION: The wide variation in fatty acid content and composition allows superior accessions to be selected for diffusion among growers. A suitable strategy would be to make a selection against PUFA content rather than just for high oleic acid. In addition, the selected high oleic accessions, before being utilized per se or as donor parents in breeding programs, have to demonstrate they are not adversely affected by the environment. © 2017 Society of Chemical Industry